Factors Affecting Compliance of Third Trimester Pregnant Women in Consuming Iron (FE) Tables - Lisa Trina Arlym; Rivi Aniah; Rukmaini (International Journal of Midwifery and Health Sciences, 2024)
Giving Fe tablets is one of the important efforts and is an effective way to prevent and overcome anemia due to iron and folic acid deficiency. To know the factors that influence the compliance of third-trimester pregnant women in consuming Iron (Fe) Tablets at Pesanggrahan Health Center, South Jakarta City in 2024.  The research design used cross-sectional. The sample of this study was 78 respondents. The data collected were secondary data using a control card sheet for taking Iron (Fe) tablets in the respondent's Maternal and Child Health Book (MCH book) and primary data using a questionnaire Data analysis was univariate and bivariate. Data analysis used a chi-square test. Pregnant women who obediently consume Fe tablets are 49 respondents (62.8%). There was a significant relationship between the variables of knowledge, attitude, and family support with the compliance of pregnant women consuming Fe tablets. While the variable of side effects showed no significant relationship with the compliance of pregnant women to consume Fe tablets. Based on the Odd Ratio value, it was obtained that the Knowledge Variable more dominantly influenced the condition of pregnant women in consuming Iron Tablets.  It is expected that midwives can provide information about Fe tablets so that mothers are obedient in consuming Fe tablets.